Proteomic Insights Into The Health Impacts of Cigarette Smoking: Analyzing Nicotine, Pahs, Aromatic Amines, And Aldehydes - Miah, Md Liton; Hossain, Md Fuad; Uddin, Md Ekhlas; Rahman, Md Habibur; Barua, Hridoy; Osman, Abdirizak Abdirahman; Khan, Md Abdul Aziz; Sheikh, Md Ramjan (Bioresearch Communications, 2024)
Cigarette smoking is a highly detrimental and dangerous habit that can lead to cancer. It contains numerous harmful compounds such as nicotine, polycyclic aromatic hydrocarbons (PAHs), aromatic amines, aldehydes, and various other compounds that are produced during smoking and enter the body. When these toxic substances enter the body, they can harm various systems, including the respiratory, cardiovascular, neurological, renal-urinary, reproductive, and ophthalmic systems. This study aims to identify the proteins that interact with nicotine, polycyclic aromatic hydrocarbons (PAHs), aromatic amines, and aldehydes and to predict their potential impacts on the human body. We collected data for this investigation from the STITCH, STRING, UniProtKB, and NCBI databases. Next, we inputted the fasta sequences of identified proteins into OmicsBox to perform BLAST, GO Mapping, and functional annotation analysis. This study collected 330 sequences, consisting of 44 sequences for nicotine, 88 sequences for PAHs, 88 sequences for aromatic amine, and 100 sequences for aldehydes; finally, 205 sequences were obtained after the BLAST search. The functional annotation study revealed that these compounds significantly affect human health, especially biological processes, cellular components, and molecular functions. Our study also found that these compounds have numerous effects on signaling pathways, heart health, brain, reproductive system, liver functions, kidney functions, RNA and DNA binding, molecular apoptosis, carbohydrate and protein metabolism, mitochondrion, nucleoplasm, cytosol, and various cellular components. We have identified multiple genes stimulated by nicotine, PAHs, aromatic amines, and aldehydes, including BDKRB2, GPRC1C, MGLUR3, NNMT, ALDH1B1, ALDH7, DERA, CRABP2, ADH1A, ODC1, TLR6, JMJD1, and so on. Most of the genes are responsible for lung cancer, cardiovascular diseases, and alcohol-related cancer. The act of smoking cigarettes can have detrimental effects on individuals close to the smokers, even if they do not engage in smoking due to the transmission of harmful vapor via the air. Our study demonstrated that cigarette smoking is a highly prevalent and preventable cause of cancer, heart disease, and reproductive diseases, making it imperative for individuals to be knowledgeable and resolute in their efforts to stop it. Bioresearch Commu. 11(1): 1651-1678, 2025 (January)